Sidang Keliling Dalam Perceraian (International Forum of Researchers and Lecturers, 2023)
In Aceh Province, the Religious Court is called the Sharia Court, each district or city has its own Sharia Court office which is located in the district or city. As stated in Law Number 3 of 2006 concerning amendments to Law Number 7 of 1989 concerning Religious Courts that: